2019
DOI: 10.1107/s205979831900754x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of the naturally fused CS and cytochrome b 5 reductase (b 5R) domains of Ncb5or reveal an expanded CS fold, extensive CS–b 5R interactions and productive binding of the NAD(P)+ nicotinamide ring

Abstract: PDB references: naturally fused CS and b 5 R domains of human Ncb5or, complex with NAD + , 6mv1; complex with NADP + , 6mv2Supporting information: this article has supporting information at journals.iucr.org/d Crystal structures of the naturally fused CS and cytochrome b 5 reductase (b 5 R) domains of Ncb5or reveal an expanded CS fold, extensive CS-b 5 R interactions and productive binding of the NAD(P) + nicotinamide ring Ncb5or (NADH-cytochrome b 5 oxidoreductase), a cytosolic ferric reductase implicated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…These NCB5Rs, which have the ability to bind NADPH, are formed through genetic mutations, which seriously affect the physiological function of the host . In addition, the structure and sequence alignment showed that, compared with NCB5R3 from animals, the Cyt b 5 R domain of Ncb5or was more closely related to the single-domain NCB5Rs from plants, fungi, and some protists . This study indicates that a natural form of NCB5R accepting NADPH is likely to exist in plants, fungi, and protists.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…These NCB5Rs, which have the ability to bind NADPH, are formed through genetic mutations, which seriously affect the physiological function of the host . In addition, the structure and sequence alignment showed that, compared with NCB5R3 from animals, the Cyt b 5 R domain of Ncb5or was more closely related to the single-domain NCB5Rs from plants, fungi, and some protists . This study indicates that a natural form of NCB5R accepting NADPH is likely to exist in plants, fungi, and protists.…”
Section: Introductionmentioning
confidence: 80%
“…At room temperature, 0.2 mL of reaction mixture contains 0.4 mM DCIP, 0.5 μg of pure protein and 100 mM potassium phosphate buffer (pH 7.0). When 0.25, 0.5, 1.0, 2.0, and 4.0 mM NAD­(P)H were added to the mixture, the absorbance changes at 600 nm were recorded every 10 s for 10 min using Thermo Scientific Fluoroskan Ascent, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The N -terminal b5 domain is linked to the C-terminal b5R domain via a CS ( C HORD- S GT1) domain, comprised of roughly 90 amino acid residues and nine β-sheets ( 55 ). The CS domain of CYB5R4 differs from its structural homologs, featuring an additional β-sheet structure involving residues G256 and P267, forming two strands (β8 and β9) separated by a five-residue loop that orient in an antiparallel fashion ( 125 ). Beyond P267, a classic type I β-turn from R268 and T271 forms a linkage to the b5R domain ( 125 ).…”
Section: Cyb5r4mentioning
confidence: 99%
“…The reason it may be highly expressed in the brain is unknown, but it may be related to its interaction with Rac, a member of the Ras superfamily (Courilleau et al 2000). NCB5or (NADH-cytochrome b 5 oxidoreductase) is implicated in diabetes and neurological diseases, but the role of Hsp90 in these functions is unclear (Benson et al 2019).…”
Section: P23-like Cochaperones That Contain Cs Domainsmentioning
confidence: 99%